1996
DOI: 10.1088/0953-8984/8/43/020
|View full text |Cite
|
Sign up to set email alerts
|

Incommensurate ordered phase in non-stoichiometric tantalum carbide

Abstract: By the neutron diffraction structure analysis method, an ordered phase of non-stoichiometric tantalum carbide with the base B1(NaCl) structure has been detected. It is shown that the superstructural reflections observed correspond to an incommensurate superstructure close to type. With allowance for ordering of , the phase diagram of the Ta - C system has been calculated and constructed. The effects of non-stoichiometry and ordering on the period of a base B1-type lattice of tantalum carbide and on the super… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0
1

Year Published

1999
1999
2015
2015

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 19 publications
(36 reference statements)
2
15
0
1
Order By: Relevance
“…Furthermore, the average atomic number difference between the approximate compositions TaC 0.95 and TaC 0.92 (a very conservative estimate of local carbon loss) is 0.45. Atomic phase contrast can be observed readily for average atomic number differences as low as 0.1, and as low as 0.01 under certain circumstances [91]. Thus, it appears that TaC sublimation could produce the brighter phase contrast observed in Fig.…”
Section: Type III Pore Formationmentioning
confidence: 78%
See 1 more Smart Citation
“…Furthermore, the average atomic number difference between the approximate compositions TaC 0.95 and TaC 0.92 (a very conservative estimate of local carbon loss) is 0.45. Atomic phase contrast can be observed readily for average atomic number differences as low as 0.1, and as low as 0.01 under certain circumstances [91]. Thus, it appears that TaC sublimation could produce the brighter phase contrast observed in Fig.…”
Section: Type III Pore Formationmentioning
confidence: 78%
“…Local temperatures are known to approach the adiabatic flame temperature for highly exothermic self-propagating reactions. Bakshi et al [34] observed melting between TaC and carbon nanotubes when using spark plasma sintering temperatures of 2123 K, which was attributed to local hot spots and indicates that local temperatures could be higher than the eutectic melting temperature of 3680 K [91]. Such a mechanism could also account for the effect of carbon surface area on grain growth and pore formation that was observed by Talmy et al [35].…”
Section: Type II Pore Formationmentioning
confidence: 92%
“…11), ÄÔÇ ÒÓÇÄÓÂÜÇÐËâ ÃÇÔÒÑÓâAEÑÍ ë ÒÑÓâAEÑÍ Ä ÍÂÓ-ÃËAEÇ ÄÂÐÂAEËâ VC y âÄÎâáÕÔâ ×ÂÊÑÄÞÏË ÒÇÓÇØÑAEÂÏË ÒÇÓÄÑÅÑ ÓÑAEÂ.´ÂÍÑÌ ÉÇ ÄÞÄÑAE ÔAEÇÎÂÐ Ä [51,52] . 170, å 1] ±²¦£²¡»¦¯ªÁ ¢¦³±°²Á¥°¬ ë ±°²Á¥°¬ ª ¶¡©°£½¦ ²¡£¯°£¦³ªÁ ¶ÂÊÑÄÞÇ ÅÓÂÐËÙÞ AEÄÖØ×ÂÊÐÑÌ ÑÃÎÂÔÕË (VC y V 8 C 7 ) ÒÓË ÐÂÎËÚËË Ö ×ÂÊÞ V 8 C 7 ÑÃÎÂÔÕË ÅÑÏÑÅÇÐÐÑÔÕË ÓÂÔÔÚË-ÕÞÄÂÎË Ô ÒÑÏÑÜßá ÖÓÂÄÐÇÐËÌ ÐÂÎßÐÞÌ ÍÂÓÃËAE a- Ta [76]. ±ÑÎÑÉÇÐËÇ ÓÑÏÃÑàAEÓËÚÇÔÍÑÌ ×ÂÊÞ z-Ta4C3 AEÂÐÑ Ä ÔÑÑÕÄÇÕÔÕÄËË ÔÑ [170]; àÕ ×ÂÊ ÐÇ âÄÎâÇÕÔâ ÖÒÑÓâAEÑÚÇÐÐÑÌ ×ÂÊÑÌ ÍÂÓÃËAE TaC y Ë ÑÃÓÂÊÖÇÕÔâ ÒÓË ÕÇÏÒÇÓÂÕÖÓÇ ÐËÉÇ 2450 K. [190 ë 193].…”
Section: ¶âêñäþç Aeëâåóâïïþ ôëôõçïunclassified
“…• C, a Knoop hardness of 2000 kg/mm 2 [4] and a superconducting transition temperature of ∼10 K. The material has attracted much interest, but good understanding has been elusive because, as in other transition metal carbides and nitrides [5][6][7][8][9][10][11][12], TaC exists over a wide range of compositions outside stoichiometry and its physical properties vary as a consequence. Mechanical, thermal, electrical and optical properties have been investigated from both theoretical and experimental points of view [13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%